Formulation and Characterization of Transfersomal Containing Breadfruit Leaves (Artocarpus altilis (Park.) Fsb.) Ethanolic Extract - Elsa Fitria Apriani; Fitrya Fitrya; Hannan Hanifah (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2022)
Breadfruit (Artocarpus altilis (Park.) Fsb.) leaves have anti-tyrosinase activity due to their flavonoid content. Anti-tyrosinase penetration is deep because the tyrosinase process occurs in the stratum basale. This study aimed to formulate and characterize the transfersomal containing breadfruit (Artocarpus altilis (Park.) Fsb.) leaves ethanolic extract with varying concentrations of Tween 80 and Phospholipon 90G. Breadfruit leaves were extracted using 96% ethanol and quantitative measures of flavonoid content. Breadfruit leaves extract was then formulated into transfersomes using the thin layer hydration method with a concentration ratio of Tween 80 and Phospholipon 90G, respectively, of 5:95; 10:90; 15:85; 20:80; and 25:75. The resulting transfersomes were then characterized by the value of entrapment efficiency (EE), polydispersity index, particle size, and zeta potential to determine the best formula. The %EE result for the 5th formula were 95.13%; 95.42%; 92.78%; 90.48%; and 87.58. The polydispersity result respectively were 0.232; 0.427; 0.236; 0.425; and 0.292. The particle sizes were 276.13 nm, 290.70nm, 222.13nm, 320.80nm, and 280.90 nm. Meanwhile, the zeta potential values respectively were -15.1; -18.2 mV; -20.5 mV; -36.9 mV; and -16.7mV. The concentrations of 20% Tween 80 and 80% Phospholipon 90G were chosen as the best formulas based on the results of their characterization. The best formula also showed a spherical morphology and was most stable with the lowest reduction of entrapment efficiency of 1.7416±0.2033%.